2012
DOI: 10.1038/jid.2012.187
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Leukocytes in Prenatal Human Dermis

Abstract: The adult human skin harbors a variety of leukocytes providing immune surveillance and host defense, but knowledge about their ontogeny is scarce. In this study we investigated the number and phenotype of leukocytes in prenatal human skin (dermal dendritic cells (DDCs), macrophages, T cells (including FoxP3 + regulatory T cells), and mast cells) to unravel their derivation and to get a clue as to their putative function in utero . By flow cytometry and immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 53 publications
(90 reference statements)
8
42
0
Order By: Relevance
“…In summary, the present study identified for the first time expression of selected AMPs in developing human skin, corroborating both the structural maturity of the skin and the advanced state of the innate immune system at the end of the second trimester [4, 7, 8, 11, 19, 20]. …”
Section: Discussionsupporting
confidence: 77%
“…In summary, the present study identified for the first time expression of selected AMPs in developing human skin, corroborating both the structural maturity of the skin and the advanced state of the innate immune system at the end of the second trimester [4, 7, 8, 11, 19, 20]. …”
Section: Discussionsupporting
confidence: 77%
“…Mast cells are observed only after 11 weeks of gestation and then increase in the second trimester. 13 Currently, the impact of premature birth, that is, when the epidermis is not fully formed, on LC proliferation is unknown but of clinical importance in lateonset sepsis.…”
Section: Discussion Fetal Skin Developmentmentioning
confidence: 99%
“…Thus, the sequential acquisition of surface markers not only resembled the murine but also human ontogeny and corroborates the notion that CD45 + precursors colonized the epidermis, where they sequentially acquire their phenotype. Given that: (1) T cells are not present in prenatal skin before 18 weeks EGA (Di Nuzzo et al, 2009;Schuster et al, 2012); (2) no other immune cells exist with a tropism for the epidermis; and (3) apoptosis is not detectable in first trimester epidermal leukocytes, we assume that CD45 + CD36 -HLA-DR -cells in embryonic skin are LC precursors. CD45 + HLA-DR -cells were also identified in the epidermis of healthy adult skin, but these cells most probably are lymphocytes as previously reported (Foster and Elbe, 1997).…”
Section: Similarities Between Lc Development In Mice and Humansmentioning
confidence: 99%